2016
DOI: 10.2174/1874471008666151027154148
|View full text |Cite
|
Sign up to set email alerts
|

Small-Animal Molecular Imaging for Preclinical Cancer Research: μPET and μSPECT

Abstract: Due to different sizes of humans and rodents, the performance of clinical imaging devices is not enough for a scientifically reliable evaluation in mice and rats; therefore dedicated small-animal systems with a much higher sensitivity and spatial resolution, compared to the ones used in humans, are required. Smallanimal imaging represents a cutting-edge research method able to approach an enormous variety of pathologies in which animal models of disease may be used to elucidate the mechanisms underlying the hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Despite the limitations due to low spatial resolution, in the field of nuclear medicine, radiomics is developing as an equal to traditional radiology, taking advantage of the information functional that this can offer. In particular, in the radiomic scope, PET is the most promising test, and several studies suggested that PET acquisition radiomics analysis could provide a valid support in the diagnosis, staging, and characterization of various tumors [ 65 ].…”
Section: Functional Imagingmentioning
confidence: 99%
“…Despite the limitations due to low spatial resolution, in the field of nuclear medicine, radiomics is developing as an equal to traditional radiology, taking advantage of the information functional that this can offer. In particular, in the radiomic scope, PET is the most promising test, and several studies suggested that PET acquisition radiomics analysis could provide a valid support in the diagnosis, staging, and characterization of various tumors [ 65 ].…”
Section: Functional Imagingmentioning
confidence: 99%
“…18 F-FDG PET/CT is the most common molecular imaging technique for preoperative staging of various malignancies, due to the higher metabolic rate of cancerous cells compared to normal ones [ 39 , 40 , 41 , 42 ], however, as a glucose analog, 18 F-FDG is excreted in urine and therefore it physiologically accumulates in the bladder, thus eventually masking the uptake of any superficial wall lesions and/or of the adjacent lymph nodes [ 43 ].…”
Section: 18 F-fdg Pet/ct For Preoperative Lymph Node Staging Of Mibcmentioning
confidence: 99%
“…Although, only one not updated meta-analysis showed a pooled sensitivity of 0.82 and specificity of 0.89 for metastatic lesion detection [38]. 18 F-FDG PET/CT is the most common molecular imaging technique for preoperative staging of various malignancies, due to the higher metabolic rate of cancerous cells com-pared to normal ones [39][40][41][42], however, as a glucose analog, 18 F-FDG is excreted in urine and therefore it physiologically accumulates in the bladder, thus eventually masking the uptake of any superficial wall lesions and/or of the adjacent lymph nodes [43]. Intense glucose metabolism in the primary tumor higher than FDG urinary excretion is present (A).…”
Section: F-fdg Pet/ct For Preoperative Lymph Node Staging Of Mibcmentioning
confidence: 99%
“…Because of the pathophysiological similarities between vertebrate mammals and humans, vertebrate mammals are widely used as models to study human disease and functions [1][2][3][4][5][6][7]. Mouse and rat comprise approximately 99.3% of mammals used in preclinical research in the USA [8].…”
Section: Introductionmentioning
confidence: 99%